Psychological Communication and Islamic Integration in Mental Health Education Via Instagram - Ramadhani, Suci; Aritonang, Idris; Barus, Liza Nuarida Ulfah Br.; Lubis, Lahmuddin (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to analyze the application of communication psychology in the content and user interactions of the Instagram account @dinamisbiropsikologi in delivering mental health education integrated with Islamic values. The research employs a qualitative approach with content analysis methods. Data were obtained from six Instagram posts in 2025, selected purposively based on two main criteria: (1) themes relevant and engaging in the context of mental health education and the integration of Islamic values, and (2) high levels of user interaction, assessed through the number of likes, comments, and responses from the admin. Data analysis was conducted systematically using NVivo software for coding and thematic categorization. The findings reveal that @dinamisbiropsikologi consistently applies principles of communication psychology, such as empathy, positive reinforcement, and affirmative language, in delivering educational messages. Islamic values are contextually integrated through direct references to Qur’anic verses and hadiths relevant to mental health themes. Strong user responses to content on self-reflection, anxiety, and stoic principles of tranquility underscore the effectiveness of this approach in building emotional connections and raising awareness of the importance of mental health, both from a general and Islamic perspective. Theoretically, this study enriches the field of communication psychology by presenting a model of integration between psychological principles and religious values in digital media. Practically, it provides insights for psychology practitioners and Islamic media managers to develop more adaptive, empathetic, and spiritually grounded communication strategies in delivering mental health education.